Delivery of silver sulfadiazine and adipose derived stem cells using fibrin hydrogel improves infected burn wound regeneration - Banerjee, Jaideep (PLoS One, 2019)
Infection control is necessary for improved burn wound regeneration. In this study contact burn wounds were induced on the dorsum of the rats and were infected with Pseudomonas aeruginosa (10(7)cfu/ml of saline) and left overnight (12–14 hours) to establish the infection. After 12 hours, the wounds were treated with PEGylated fibrin hydrogel containing 50 mgs of silver sulfadiazine (SSD) loaded chitosan microsphere (SSD-CSM-FPEG). On day 9, SSD-CSM-FPEG treated burn wounds further received adipose derived stem cell (5×10(4) ASCs cells/ml) embedded in PEGylated fibrin hydrogel. Wounds were assessed for the healing outcomes such as neovascularization, granulation tissue formation, wound closure and collagen maturation. Analysis of bacterial load in the burn wound biopsies, demonstrated that SSD–CSM-FPEG significantly reduced bacterial infection, while overt infection was still observed in the untreated groups on day 14. Sequential treatment of infected wounds with SSD–CSM-FPEG followed by ASC-FPEGs (SSD-CSM-ASC-FPEG) significantly reduced bacterial colonization (9 log reduction) and pro-inflammatory cytokine (TNF-α) expression. A significant increase in neovascularization markers; NG2 and vWF was also observed. Histological analysis indicated the wounds treated with SSD-CSM-ASC-FPEG increased amount of dermal collagen matrix deposition, a thicker granulation tissue on day 21 and more mature collagen on day 28. This work demonstrates that the sequential treatment of infected burn wounds with SSD-CSM-FPEG followed by ASC-FPEG reduces bacterial infection as well as promotes neo-vascularization with improved matrix remodeling.